Strategic management of Russian metallurgy in the context of challenges and risks - Yu. Yu. Kostyukhin (Управленческие науки)
The subject of the study is Russian metallurgical companies, which in the context of the transformation of the economy, taking into account the difficult geopolitical situation, need to move from a recovery strategy to a strategy of progressive growth. The latter, taking into account the factors that ensure the success of Russian companies in the metal market, should become a tool for effective management, as well as for predicting business risks. The article presents the riskdominating elements and macroeconomic indicators for building an effective strategy for the development of enterprises in the metallurgical industry, which will allow for a comprehensive assessment of the situation and making rational and effective management decisions to increase the competitiveness of companies, their adaptability to modern factors of the external environment, the growth of economic potential and capitalization. The peculiarity of the study is to identify the dominant factors of entrepreneurial risk and improve ways to increase the investment attractiveness of the company.